Insulin like growth factor-I, insulin like growth factor binding protein-1, and insulin in childhood Crohn's disease. Issue 7 (July 1993) - Thomas, A G; Holly, J M; Taylor, F; Miller, V
Abstract : Twenty nine children with Crohn's disease were studied before and after treatment with steroids or an elemental diet to assess the effect of disease activity and treatment on serum insulin like growth factor I (IGF-I), insulin like growth factor binding protein (IGFBP-1), and insulin concentrations. The median serum IGF-I concentration was lower in patients with active disease than in matched controls, and lower in stunted than well grown patients, but insulin and IGFBP-1 concentrations were not significantly different between any group. After four weeks of either treatment there was an increase in the median serum IGF-I concentration; this was greater in the steroid group than the elemental diet group. The median serum insulin concentration increased and median serum IGFBP-1 concentration decreased in the steroid treated group but not in the elemental diet group. These changes were accompanied by a greater and more sustained increase in energy intake in the steroid group. Despite this the median height velocity SD score was greater in the elemental diet group than in the steroid group.